Analysis of Red Betel Leaf Tests As A Natural Anti-Infection In Post Partum Mothers - Yudhia Fratidhina; Sri Mulyati; Hetty Astri; Silvester Maximus (Women, Midwives and Midwifery, 2023)
Background: Incidence of infection contributes to maternal mortality. Innovative efforts to treat infection in postpartum mothers continue to be made, including non-pharmacological techniques. The local wisdom of red betel leaves is believed by the community to be able to handle it. The true efficacy of this extraordinary red betel leaf deserves further investigation. The purpose of this study was to assess the effectiveness of red betel on perineal wound healing in postpartum mothers. Methods: This study used the Quasi Experiment with Control Group Design method. The study was conducted on 80 postpartum mothers with perineal wounds degrees 1 to 3. 40 women were included in the intervention group who were given red betel ointment made by researchers from 2 hours to 7 days postpartum. 40 people as the control group were given perineal wound care according to standard. Assessment of wound healing was carried out every day until the 7th day postpartum. Statistical tests used the dependent and independent t-tests to examine differences in healing scores in the two study groups. Results: There was an increase in the average perineal wound healing value in the intervention group which was higher and there was an increase in the average healing value every day, starting from the first day (mean = 9.25), the second day (mean = 11.55), and the seventh day (mean = 12.65) compared to the control group, p value <0.001. On the third day postpartum, the intervention group had the maximum healing value (100%) compared to the control group (52.5%)